3(3x-1)=8(x+1)

Simple and best practice solution for 3(3x-1)=8(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-1)=8(x+1) equation:


Simplifying
3(3x + -1) = 8(x + 1)

Reorder the terms:
3(-1 + 3x) = 8(x + 1)
(-1 * 3 + 3x * 3) = 8(x + 1)
(-3 + 9x) = 8(x + 1)

Reorder the terms:
-3 + 9x = 8(1 + x)
-3 + 9x = (1 * 8 + x * 8)
-3 + 9x = (8 + 8x)

Solving
-3 + 9x = 8 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-3 + 9x + -8x = 8 + 8x + -8x

Combine like terms: 9x + -8x = 1x
-3 + 1x = 8 + 8x + -8x

Combine like terms: 8x + -8x = 0
-3 + 1x = 8 + 0
-3 + 1x = 8

Add '3' to each side of the equation.
-3 + 3 + 1x = 8 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 8 + 3
1x = 8 + 3

Combine like terms: 8 + 3 = 11
1x = 11

Divide each side by '1'.
x = 11

Simplifying
x = 11

See similar equations:

| 13x-11=-180 | | 2x+x+2(2)+103=180 | | 1.4*k=2.52 | | 3(3s+4)=111 | | 4x-5(3x+6)=-19 | | 6(2l+3)=102 | | 5x-40=36+x | | 28x+160=144 | | 4z-(2y-x)= | | 4(a-2)=44 | | 2z^2-5z=12 | | 2x+x+2(2)+39=180 | | 4ab+a= | | 7p+2=5p+9 | | -7=-2+U | | 7x-110=64+x | | 62+2+3x=62 | | 2236000+-17740x=-71.2514 | | 4/5x+2/5=4/5 | | (9-4)*3=12 | | f(x)=2(0.75) | | 3x-20=7x-4 | | 2x+x+2(2)+89=180 | | 15r^2=-7r+4 | | 7x-37=29+4x | | 30+8y=-7y | | (14x-22)(x+11)=240 | | 4y-12=14 | | 2y-7x=-10 | | 3x+2[x+7]-5=4[x+3]-3[x+1] | | 20x-15=-8 | | 8w^2-18+9= |

Equations solver categories